The Effect of Raffinose and Methionine on Frozen/Thawed Angora Buck (Capra hircus ancryrensis) Semen Quality, Lipid Peroxidation, and Antioxidant Enzyme Activities. - Bucak, Mustafa Numan; Tuncer, Purhan Barbaros; Sariozkan, Serpil; Atessahin, Ahmet; Yeni, Deniz; Avdatek, Fatih (Soc Study Reproduction, 2010)
[Abstract Not Available]
43rd Annual Meeting of the Society-for-the-Study-of-Reproduction -- JUL 31-AUG 03, 2010 -- Milwaukee, WI